Finding a place for the e-cargo bike: The parking and insurance practices of owners in Ireland - Caulfield, Brian; Egan, Robert (My University, 2025)
E-bikes and e-cargo bikes can ‘extend’ the practice of cycling, reducing the physical demands of cycling further, cycling faster, cycling in varied topography and weather, and cycling with passengers and goods. However, while e-cycling can moderate the demands of cycling and expand its functional capabilities, it can also introduce new physical and technical competences. The competences of parking may be particularly intensified. The higher values, additional components, and heavier weights of an e-cycle can mean greater and more complex use of locks, more cautious placing, and more laborious manoeuvring. In this qualitative study, we explored e-cargo bike owner experiences and practices of parking in the context of Ireland. We found that participants struggled to find a place that was a secure and convenient to park their e-cargo bikes. This struggle shaped their everyday mobility, constraining how and where the e-cargo bike would be used. In this paper, we conceptualise the dominant parking styles that participants adopted at home, at work, and in public, to enable secure and convenient e-cargo bike parking: standing out, official anchoring, improvised anchoring, and locking away. In addition, we provide an analysis of insurance measures adopted by participants to safeguard the e-cargo bike in the instance of damage or theft, and how insurance measures – and the absence of insurance – can structure parking styles. To conclude, we make several observations on cycle parking planning that could help to advance more e-cargo-bike-inclusive cycle parking futures in the context of Ireland.
PUBLISHED
Keywords: Cycling; E-cargo bike; E-bike; Parking; Insurance; Practice theory; E-vélomobility; Smart & Sustainable Planet; Environmental aspects of transportation; Transport